First determination of the spin-parity of Ξc(3055)+,0 Baryons - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
The Ξ0⁢(−)𝑏→Ξ𝑐⁢(3055)+(0)⁢(→𝐷+(0)⁢Λ)⁢𝜋− decay chains are observed, and the spin-parity of Ξ𝑐⁢(3055)+(0) baryons is determined for the first time. The measurement is performed using proton-proton collision data at a center-of-mass energy of √𝑠 =13 TeV, corresponding to an integrated luminosity of 5.4 fb−1, recorded by the LHCb experiment between 2016 and 2018. The spin-parity of the Ξ𝑐⁢(3055)+(0) baryons is determined to be 3/2+ with a significance of more than 6.5⁢𝜎 (3.5⁢𝜎) compared to all other tested hypotheses. The up-down asymmetries of the Ξ0⁢(−)𝑏→Ξ𝑐⁢(3055)+(0)⁢𝜋− transitions are measured to be −0.92±0.10±0.05 (−0.92±0.16±0.22), consistent with maximal parity violation, where the first uncertainty is statistical and the second is systematic. These results support the hypothesis that the Ξ𝑐⁢(3055)+(0) baryons correspond to the first 𝐷-wave 𝜆-mode excitation of the Ξ𝑐 flavor triplet.